In chronic spontaneous urticaria, IgE and C-reactive protein are linked to distinct microRNAs and interleukin-31 - Bakay, Ozge Sevil Karstarli; Demir, Betul; Cicek, Demet; Erol, Deniz; Asci Toraman, Zulal; Gural, Yunus; Maurer, Marcus (Wiley, 2023)
BackgroundChronic spontaneous urticaria (CSU) is a common and disabling disease. Assessments of IgE and C-reactive protein (CRP) are recommended in the diagnostic work-up, but the role and clinical relevance of these biomarkers are not well characterized. Moreover, it remains unknown if elevated levels of IgE or CRP are linked to CSU microRNA (miRNA) signatures or interleukin 31 (IL-31). MethodsWe measured IgE and CRP serum levels in 47 CSU patients (and 45 healthy controls) and determined CSU disease activity using the urticaria activity score (UAS7). Expression levels of miR-155 and miR-221 were assessed by RT-PCR, and IL-31 levels were determined by ELISA. ResultsTotal IgE and CRP levels were independently increased in CSU patients. IgE and CRP levels were highest and lowest in patients with high and mild disease activity. IgE levels correlated with miR-155 levels, whereas CRP levels correlated with miR-221 levels. miR-155 and miR-221 were significantly overexpressed in CSU patients. ROC analyses linked miRNA-155 and CSU with a sensitivity of 79% and specificity of 87%, and miRNA-221 and CSU with a sensitivity of 75% and specificity of 91%. High CRP and miR-221 expression levels were linked to elevated levels of IgG anti-TPO and IL-31. ConclusionIgE and CRP are useful biomarkers for disease activity in CSU, with distinct miRNA profiles. High CRP and miR-221 levels may point to autoimmune CSU and a role for IL-31.
Keywords: CRP; IgE; interleukin-31; micro-RNA; urticaria